2022
DOI: 10.1111/tbed.14677
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis vectors in the environment of treated leishmaniasis cases in Spain

Abstract: Transmission of leishmaniasis in endemic areas is characterized by microfocality related to the presence of the vector. Most entomological studies in southwestern Europe have focused on sylvatic areas and town outskirts, very few have sampled town or urban centres, and no survey has investigated inside households. The aim of this study was to determine the sand fly species diversity and vector density in the surroundings of human leishmaniasis cases compared with environments in which there was no association.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…We have detected L. infantum in females of cluster 1.2 (both, P. perniciosus and females with P. longicuspis morphology but P. perniciosus genetics), cluster 2 ( P. longicuspis s.s) and cluster 3 (unnamed species). None of the infected females found had a parasite load greater than 10 parasites/sand fly, while 25% typical P. perniciosus females that were infected in endemic areas had very high infection rates with more than 10,000 parasites/sand fly (Díaz‐Sáez et al, 2022) highlighting typical P. perniciosus as the main vector of L. infantum .…”
Section: Discussionmentioning
confidence: 99%
“…We have detected L. infantum in females of cluster 1.2 (both, P. perniciosus and females with P. longicuspis morphology but P. perniciosus genetics), cluster 2 ( P. longicuspis s.s) and cluster 3 (unnamed species). None of the infected females found had a parasite load greater than 10 parasites/sand fly, while 25% typical P. perniciosus females that were infected in endemic areas had very high infection rates with more than 10,000 parasites/sand fly (Díaz‐Sáez et al, 2022) highlighting typical P. perniciosus as the main vector of L. infantum .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of sand fly vectors is considered the main risk for leishmaniasis. In Spain, recent studies have reported six species of sand flies, and the most prevalent are Sergentomyia minuta and Phlebotomus perniciosus [ 48 ]. The authors analyzed the presence of L. infantum in sand flies recovered and concluded that the P. perniciousus are more related to Leishmania transmission than S. minuta.…”
Section: Discussionmentioning
confidence: 99%